ANALISIS KINERJA PEMERINTAH DESA DALAM PEMBANGUNAN INFRASTRUKTUR DI KELURAHAN RENON KECAMATAN DENPASAR SELATAN - I Wayan Wirawan; I Made Winia (Jurnal AKSES, 2020)
With the enactment of Law Number 32 of 2004 concerning Regional Government, where the implementation of government affairs by the Regional Government and DPRD according to the principle of autonomy and assistance tasks with the principle of broadest autonomy in the system and principles of the Unitary State of the Republic of Indonesia of 1945. The Central Government expects a region it can regulate the needs in the region through regional autonomy, both district / city government affairs and village government affairs so that the resolution of all problems in the region can be quickly resolved by the regional government. In practice, it turns out that Law 32/2004 does not clearly discuss what are the government instruments in the village, so a Government Regulation of the Republic of Indonesia Number 72 of 2005 concerning Villages was drafted again. In principle, this regulation contains several things, among others, which regulates village authority, village government institutions, village apparatus, village planning, and village finance. Performance (performance) is a picture of the level of achievement of the implementation of an activity / program / policy in realizing the goals, objectives, vision and mission of the organization contained in organizational strategic planning.Seeing from the problems and symptoms of the performance mentioned above, the author is interested in examining more deeply by taking the title "Analysis of Village Government Performance in Infrastructure Development in Renon District, South Denpasar District".Data sources: 1) Primary data, i.e. data obtained directly in Renon Village, South Denpasar District, Denpasar City, 2) Secondary Data, i.e. data obtained from recording official documents, books, and other readings that are can support the discussion of problems in this thesis. While the data analysis used is descriptive qualitative method which is a way of data processing which is done by systematically compiling so that a general conclusion is obtained.Based on some of the descriptions that have been submitted in Chapter IV on the Performance of Village Governments in Infrastructure Development in Renon Village, South Denpasar District, the following conclusions can be drawn:Village Government Productivity in completing Infrastructure Development in Renon Village, the village government really sees in terms of needs not wants, uses and benefits for the community is quite good.The responsiveness of the Village Government in accommodating and realizing the aspirations of the community, in capturing and following up on the aspirations of the community was considered to be good by realizing cooperation with each RT leader in Renon village to gather each RT's residents to explore the aspirations and complaints within the RT, to then be accommodated by the Renon village government.The Responsibility of the Village Government in supervising infrastructure development in the Renon Kelurahan, has supervised the infrastructure development activities that took place in each hamlet of the Renon kelurahan.Village Government Accountability in the form of Village Government Accountability Report (LPJ) to the community in the Renon Village is delivered in writing through information media at the Renon Village Office to the community through BPD and verbally through meetings in the village. Village Government Accountability in the form of Village Government Accountability Report (LPJ) to the community in villages in Renon Kelurahan is considered not optimal because the delivery is still verbally to the community through meetings in the village, there is no seriousness to make it in written form and then stick to the announcement board not yet implemented well in the village of Renon.